2015
DOI: 10.3390/buildings5030933
|View full text |Cite
|
Sign up to set email alerts
|

Configuration of Green Spaces for Urban Heat Island Mitigation and Future Building Energy Conservation in Hanoi Master Plan 2030

Abstract: Abstract:The study aims to assess the urban heat island (UHI) effects in the city under the present land use conditions as well as those conditions proposed by the Hanoi Master Plan 2030 through numerical simulation, using Weather Research and Forecasting (WRF). Furthermore, this paper assesses additional land use scenarios with different spatial and green space configurations. The results show that the implementation of the master plan does not significantly affect the peak air temperature in the built-up are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 16 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Under the HCCMP, about 28% of the natural land in 2011 will be converted to built-up land to accommodate the rising urban population of Hanoi, projected to increase to~9.2 million by 2030 [21]. As a result of the higher demands for housing and infrastructure, the amount of land that is built upon in the Province is projected to rise sharply, by almost three times, from 463.4 km 2 in 2011 to more than 1295 km 2 by 2030 [22]. Consequently, there is an urgent need for urban planners and local authorities to monitor and regulate the upcoming urbanization and its environmental impact.…”
Section: Hanoi Provincementioning
confidence: 99%
“…Under the HCCMP, about 28% of the natural land in 2011 will be converted to built-up land to accommodate the rising urban population of Hanoi, projected to increase to~9.2 million by 2030 [21]. As a result of the higher demands for housing and infrastructure, the amount of land that is built upon in the Province is projected to rise sharply, by almost three times, from 463.4 km 2 in 2011 to more than 1295 km 2 by 2030 [22]. Consequently, there is an urgent need for urban planners and local authorities to monitor and regulate the upcoming urbanization and its environmental impact.…”
Section: Hanoi Provincementioning
confidence: 99%
“…At the first step, based on the method introduced by Nik [50], the weather data were developed based on the typical and extreme weather conditions of Stockholm. Then, the urban models were generated in Rhinoceros/Grasshopper based on building modular cells or 'BMC' [42]. The models were transferred to Autodesk CFD using Autodesk Inventor to define computational domains and boundary conditions.…”
Section: Cfd and Epsmentioning
confidence: 99%
“…The main factors in the urban microclimate that have been investigated include air temperature [35], surface temperature [36], solar radiation [37], wind flow variations [38], and air humidity [39]. Many works have studied the UHI effect on the energy performance of buildings [40,41] and its impacts on higher cooling demand in cold regions and lower heating demand in hot-arid regions [42,43] in urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that although sensible cooling loads increased with the increase in outdoor temperature, the latent cooling loads decreased due to the decrease in absolute humidity and the increase in air temperature. Trihamdani et al [31] assessed the UHI effects in the city under the present land use conditions, as well as those conditions proposed by the Hanoi Master Plan 2030 through numerical simulation, using Weather Research and Forecasting (WRF). They found that the peak air temperature in the built-up areas (approximately 1 • C higher at the maximum) was not significantly modified, but high temperature areas, with temperatures of 40-41 • C, would expand widely over the new built-up areas.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature survey, state-of-the-art of correlations between UHI or SUHI and land-use composition are being widely analyzed in the recent years. In contrast, the study of UHI or SUHI with respect to Hanoi City Master Plan 2030 is rather limited; for example, about spatial energy consumption [30], assessment of UHI effects based on WRF simulations [31]. Then, what would be the most updated status of land use change with respect to the city Master Plan?…”
Section: Introductionmentioning
confidence: 99%